PENGARUH RASIO PERPUTARAN MODAL KERJA, RASIO PERPUTARAN KAS, DAN RASIO AKTIVA LANCAR DENGAN TOTAL AKTIVA TETAP TERHADAP RETURN ON INVESTMENT PADA BANK RAKYAT INDONESIA - WAHYUL . (LP2MTBM MAKARIOZ, 2020)
Low profit margin or low asset turnover results in low Return on Investment. This study aims to determine whether there is aneffect of working capital turnover ratio, cash turnover ratio, and the ratio of total current assets to total assets to return oninvestment simultaneously and partially at PT. Bank Rakyat Indonesia Tbk for the period 2014-2020. The data used in thisresearch is secondary data, namely the audited and published financial reports of the banking company Bank RakyatIndonesia (BRI). The data analysis technique used is descriptive quantitative analysis and multiple linear regression. Theresults of multiple linear regression analysis in this study Y = -5999,741 + 0.51 X1 + 0.151 X2 + 0.61 X3 where the amount ofR2 = 0.960 or 96% shows the dependent variable ROI in the banking company PT. Bank Rakyat Indonesia Tbk. Is affectedby the independent variables WCTO, CTO, and CATA simultaneously. While the remaining 14.00% is explained by otherfactors which are not examined. The results of the study simultaneously the value of WCTO, CTO, and CATA have a positiveand significant effect on ROI with a value of Fcount = 166.298> Ftable = 3.07 and a significant value of Sig. 000 ≤ α0.05.Meanwhile, partially, it shows that WCTO has a positive and significant effect on ROI with tcount = 9.439> ttable = 2.074 and asignificant value of Sig. 000 <α0.05. Likewise, CTO has a positive and significant effect on ROI with a value of tcount = 2.536>ttable = 2.074 and a significant value of Sig.0.019 <α0.05. while CATA has no effect on ROI with a value of tcount = 1.614 <ttable =2.074 and a significant value of Sig.0,121> α0.05.